What drives the occurrence of the melioidosis bacterium Burkholderia pseudomallei in domestic gardens? - Mirjam Kaestli; Glenda Harrington; Mark Mayo; Mark D Chatfield; Ian Harrington; Audrey Hill; Niels Munksgaard; Karen Gibb; Bart J Currie (Public Library of Science (PLoS), 2015)
Melioidosis is an often fatal infectious disease affecting humans and animals in tropical regions and is caused by the saprophytic environmental bacterium Burkholderia pseudomallei. Domestic gardens are not only a common source of exposure to soil and thus to B. pseudomallei, but they also have been found to contain more B. pseudomallei than other environments. In this study we addressed whether anthropogenic manipulations common to gardens such as irrigation or fertilizers change the occurrence of B. pseudomallei. We conducted a soil microcosm experiment with a range of fertilizers and soil types as well as a longitudinal interventional study over three years on an experimental fertilized field site in an area naturally positive for B. pseudomallei. Irrigation was the only consistent treatment to increase B. pseudomallei occurrence over time. The effects of fertilizers upon these bacteria depended on soil texture, physicochemical soil properties and biotic factors. Nitrates and urea increased B. pseudomallei load in sand while phosphates had a positive effect in clay. The high buffering and cation exchange capacities of organic material found in a commercial potting mix led to a marked increase in soil salinity with no survival of B. pseudomallei after four weeks in the potting mix sampled. Imported grasses were also associated with B. pseudomallei occurrence in a multivariate model. With increasing population density in endemic areas these findings inform the identification of areas in the anthropogenic environment with increased risk of exposure to B. pseudomallei.